PENJATUHAN PIDANA MATI TERHADAP PELAKU PENGEDAR NARKOTIKA - Rupertus Paskalianus Iwan Leki; Hari Soeskandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The imposition of the death penalty on drug traffickers is still a long debate because it is not in accordance with the Human Rights Principles so that the application of the death penalty is still widely disputed. Indonesia as a country of law in Article 10 of the Criminal Code places the death penalty as the main crime so this is the problem because Indonesia is also a country that upholds human rights. This study aims to relent in how the death penalty is applied to drug dealers. In research is a literature study using the statutory approach method as the main source. In this study, it was found that the 1945 constitution article 28A provides guarantees for everyone to live and the right to maintain their lives as well as regulated in detail in Law Number 39 of 1999 concerning Human Rights. Of course, this is what makes it a problem because Indonesia still makes the death penalty the main crime